BELIEFS OF WOMEN REGARDING FOOD DURING LACTATION: Food During Lactation - ., Dr Uzma Hassan (Pakistan Armed Forces Medical Journal, 2013)
Objectives: To study the women’s beliefs regarding diet during lactation and to see the relationship between dietary beliefs and their educational status. Study Design: Descriptive study. Place and Duration of Study: Vaccination centre established at Paediatrics out-patient department (OPD) of Military Hospital, Rawalpindi from February to July 2006. Material and Method: One hundred and seventy mothers were interviewed by using a close ended questionnaire, based on convenience sampling technique. Data was analysed by using Statistical Package for Social Sciences (SPSS 17). Relationship between educational status and dietary beliefs was analysed and the results were considered significant if ‘r-value’ is more than 0.5 with ‘p-value’ less than 0.05. Results: It was noticed that more women were convinced that amount of diet should be increased during lactation. It was also observed that almost equal number of women had the belief that some of the foods are to be restricted or not be restricted during lactation. The concept, however, changed with education and women with higher education advocated that no food should be restricted. A positive relationship was found between the education of the respondents and their belief regarding hot and badi effects of food. Women with lesser education had strong belief about hot or cold foods. Conclusions and Recommendations: The findings reported in this study together with those previously reported by various authors, it is conclusive that the education has an influence on beliefs of the individuals. It is critically important for researchers to conduct additional research that addresses the concerns on the false beliefs so as to remove them from the society through education of health professional and the masses especially the women. The information thus obtained from the studies will help in addressing issues for improvement of nutritional knowledge and dietary practices in women.